Transitions in a West African Labour Market: The Role of Family Networks - Christophe Jalil Nordman; Laure Pasquier-Doumer (Institute for the Study of Labor (IZA), 2014)
This paper sheds light on the role of family networks in the dynamics of a West African labour market, i.e. in the transitions from unemployment to employment, from wage employment to self-employment, and from self-employment to wage employment. It investigates the effects of three dimensions of the family network on these transitions: its structure, the strength of ties and the resources embedded in the network. For this purpose, we use a first-hand survey conducted in Ouagadougou on a representative sample of 2000 households. Using event history data and very detailed information on family network, we estimate proportional hazard models for discrete-time data. We find that family networks have a significant effect on the dynamics of workers in the labour market and that this effect differs depending on the type of transition and the considered dimension of the family network. The network size appears to not matter much in the labour market dynamics. Strong ties however play a stabilizing role by limiting large transitions. Their negative effect on transitions is reinforced with high level of resources embedded in the network.
Keywords: D13; J24; L14; 330; family network; labour market dynamics; event history data; survival analysis; Burkina Faso